OF INDEPENDENT TESTING WORK STUDENTS OF TECHNICAL SPECIALTIES (CASE STUDY ON DISCIPLINE «PSYCHOLOGY OF BUSINESS COMMUNICATION») - Хоменко-Семенова, Леся Олексіївна (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
This article attempts to describe the features of independent work of students of technical specialties of discipline «Psychology of business communication.» The author argues that independent student work should be aimed at mastering the content of educational material in each discipline, the development of personality traits such as the ability to organize and implement its activities without external guidance and assistance. Research organized self-study causes activation of teaching and learning of students of technical specialties; taught to work independently on scientific and technical and methodical literature, acquire the necessary knowledge, skills and acquire practical skills for the formation of future specialists for professional work